Dupont System Analysis For Measure Financial Performance At Automotive Component Industry In Indonesia - Dhoya Safira Tresna Lestari; Postgraduate Students Paramadina University (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
The purpose of this study is to evaluate the financial performance of several automotive component industry companies in Indonesia. The research used of descriptive-quantitative research method, the research of attempted to collect and present data from companies for analysis so as to provide a fairly clear picture of the object under study. The type of data used in this research is quantitative data, namely data in the form of explanations or statements in the form of numbers, namely financial reports from several companies listed on the Indonesian Stock Exchange which are used as the population in the research, including; AUTO, ASII, DRMA, BOLT, SMSM, GJTL and INDS for the 2019-2023 period. By using the Dupont system method as an analysis method. Analysis of the Dupont system method also shows that factors such as net profit margin, asset efficiency and financial leverage influence the financial performance of companies in the automotive components industry. The results of this research explain how the dupon system determines between six similar companies providing company performance data in terms of Net Profit Margin (NPM), Total Asset Turn Over (TATO), Equity Multiplier (EM) and Return on Equity which can be used by potential investors in investing in automotive component industry companies in Indonesia.